New Media Literacy And Media Use Among University Students In Malaysia - Chin, Ying Shin; Zanuddin, Hasmah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
False information is a concern in this digital era where communication technologies, particularly social media, enable the public to consume, create, and share media content. New media literacy associated with critical thinking is of importance in keeping away from the negative influences of the widespread misleading news and information. Due to the limited studies on new media literacy in Malaysia, this study aimed to identify the levels of new media literacy among university students in Malaysia, measure the difference in new media literacy across demographic factors, and examine the relationship between media use and new media literacy. The quantitative data were collected through survey questionnaire at a private university in Malaysia. The findings showed that most of the students are at the medium level of new media literacy. No significant difference was found in new media literacy based on demographic factors, except media use which also had a small positive correlation with two dimensions of new media literacy, namely functional prosumption and critical prosumption. The findings served as a valuable input for public or private institutions or organizations that are responsible or keen in tackling fake news. © 2019, Blue Eyes Intelligence Engineering and Sciences Publication. All rights reserved.